Creating a hyperpolarised pseudo singlet state through polarisation transfer from parahydrogen under SABRE - Olaru, Alexandra M. (Royal Society of Chemistry, 2016)

(untitled) (Chem Commun (Camb))
The creation of magnetic states that have long lifetimes has been the subject of intense investigation, in part because of their potential to survive the time taken to travel from the point of injection in a patient to the point where a clinically diagnostic MRI trace is collected. We show here that it is possible to harness the signal amplification by reversible exchange (SABRE) process to create such states in a hyperpolarised form that improves their detectability in seconds without the need for any chemical change by reference to the model substrate 2-aminothiazole. We achieve this by transferring Zeeman derived polarisation that is 1500 times larger than that normally available at 400 MHz with greater than 90% efficiency into the new state, which in this case has a 27 second lifetime.